(untitled) - Gross, Jurgen H. (Berlin, Germany, 2004)
This book is tailored for students and professionals as well as novices from other fields to mass spectrometry, an indispensable tool in chemistry and life sciences. It will guide them from the basics to the successful application of mass spectrometry in their daily research. Starting from the very principles of gas-phase ion chemistry and isotopic properties, it leads through the design of mass analyzers and ionization methods in use to mass spectral interpretation and coupling techniques. Step by step the readers will learn how mass spectrometry works and what it can do as a powerful tool in their hands. The book comprises a balanced mixture of practice-oriented information and theoretical background. The clear layout, a wealth of high-quality figures and a database of exercises and solutions, accessible via the publisher?s web site, support teaching and learning.
Keywords: Mass spectrometry,Chemistry, analytic